Behavioral contrast: Research and areas for investigation. Issue 3 (16th May 2018) - Boyle, Megan A.; Hoffmann, Audrey N.; Lambert, Joseph M.
Abstract : Behavioral contrast occurs when a change in reinforcement rate in one context results in a change in behavior in the opposite direction in an unchanged context. Despite decades of study by basic researchers, behavioral contrast has remained largely an unstudied phenomenon among applied researchers. The purpose of this paper is to occasion translational and applied research on behavioral contrast with the aim of predicting and controlling socially significant behavior in unchanged contexts. We present a brief history of contrast and related definitions, review research with human and nonhuman subjects, and suggest future directions for applied and translational researchers.